Distributed applications and interoperable systems : 19th IFIP WG 6.1 International Conference, DAIS 2019, held as part of the 14th International Federated Conference on Distributed Computing Techniques, DisCoTec 2019, Kongens Lyngby, Denmark, June 17-21, 2019, Proceedings /: 19th IFIP WG 6.1 International Conference, DAIS 2019, held as part of the 14th International Federated Conference on Distributed Computing Techniques, DisCoTec 2019, Kongens Lyngby, Denmark, June 17-21, 2019, Proceedings. (2019) - Unknown
No abstract available